2009
DOI: 10.1007/s12274-009-9049-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes inhibit the hemolytic activity of the pore-forming toxin pyolysin

Abstract: Functionalized carbon nanotubes have already demonstrated great biocompatibility and potential for drug delivery. We have synthesized acid oxidized and non-covalently PEGlyated single-walled carbon nanotubes (SWNTs), which were previously prepared for drug delivery purposes, and explored their potential for detoxifi cation in the bloodstream. Our investigations of the binding of SWNTs to a pore-forming toxin pyolysin show that SWNTs prevented toxin-induced pore formation in the cell membrane of human red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As seen from Figure scanning electron microscopy of red blood cells subjected to PLO [32] or with the pore sizes measured for other members of the cholesterol-dependent cytolysins family [33].…”
Section: Visualization Of Plo Oligomers In Tblmsmentioning
confidence: 96%
“…As seen from Figure scanning electron microscopy of red blood cells subjected to PLO [32] or with the pore sizes measured for other members of the cholesterol-dependent cytolysins family [33].…”
Section: Visualization Of Plo Oligomers In Tblmsmentioning
confidence: 96%
“…Although the good safety profile, biodegradability, and relative manufacturing simplicity make liposomes and ILEs attractive options, ILEs are often criticized for their lack of stability and limited chemical diversity. In recent years, a considerable amount of work has been invested into the development of other biodetoxifying nanostructures, including nanospheres, nanocapsules, and nanotubes (21)(22)(23). Several studies have reported good extraction efficiencies for drugs or heavy metals under in vitro conditions using nanoparticles, but most of the systems investigated so far do not possess optimal properties for an antidotal application in vivo.…”
Section: Liposomesmentioning
confidence: 99%
“…Several studies have reported good extraction efficiencies for drugs or heavy metals under in vitro conditions using nanoparticles, but most of the systems investigated so far do not possess optimal properties for an antidotal application in vivo. The high surface charge (21), nonbiodegradability (23), and/ or hemolytic effects (22) of several tested systems preclude clinical use, especially considering the high doses that are often needed to counteract the overdosed drugs.…”
Section: Liposomesmentioning
confidence: 99%
“…Using confocal microscopy, Sachar and Saxena (2011) showed that the fluorescent-tagged SWNTs may enter into the erythrocytes through a passive mechanism after 1 h exposure (Sachar and Saxena 2011), whereas Raman spectroscopic data from Donkor et al (2009) suggests that there was no evidence of uptake by erythrocytes after 2 h incubation with SWNTs (Donkor et al 2009). Given the absence of endocytic receptors on normal mature erythrocytes, it is plausible that the uptake of SWNTs by erythrocytes, as reported by Sachar and Saxena (2011) may have been occurred through other mechanism(s), such as passive uptake, which has been shown with titanium dioxide, polystyrene, and gold nanoparticles (Geiser et al 2005;Rothen-Rutishauser et al 2006); the SWNTs might also have been associated with the erythrocyte membrane instead of entering the cells.…”
Section: Molecular Mechanisms Of Swnts Nanotoxicitymentioning
confidence: 99%